ISLAMIC COUNSELING FRAMEWORK FOR DEALING WITH AI-BASED DIGITAL GRIEF (BARZAKH DIGITAL) - Mawaddati, Arini; Maram, Ahmad Nabilul; Firtiyah, Lilis (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
The rapid emergence of Artificial Intelligence (AI) has led to the creation of "griefbots" and "digital afterlife" technologies, which simulate interaction with the deceased. This development raises critical, unexamined questions about its impact on bereavement within established religious frameworks. This paper aims to analyze the theopsychological and ethical implications of these technologies from the perspective of Islamic counseling. This study employs a qualitative, library-based research design. It conducts a thematic and comparative analysis of two distinct bodies of literature: classical Islamic texts on spiritual psychology and contemporary academic literature on the psychological and ethical dimensions of grief technology. The findings reveal a profound conflict between the function of griefbots and the Islamic framework for grief. The technology's "illusion of continuity" fundamentally contradicts the core Islamic principle of accepting God's decree (qadr), thus impeding healthy mourning. Furthermore, the artificial dependency fostered by these simulations undermines the spiritual practice of reliance on God (tawakkul), replacing it with a technological surrogate. From an ethical perspective based on the objectives of Islamic law (maq??id al-shar??ah), the technology is identified as a potential source of harm (mafsadah) to an individual's faith and intellect. The study concludes that AI-driven grief technologies are spiritually and psychologically incongruent with a healthy Islamic grieving process. This necessitates the development of a specialized therapeutic approach. The primary implication is the proposed Islamic counseling framework, which provides practical, theologically grounded strategies for guiding individuals away from digital illusions and toward authentic spiritual healing.